Hacking planned obsolescense in robotics, towards security-oriented robot teardown - Mayoral-Vilches, Victor; Glera-Picón, Alfonso; Ayúcar-Carbajo, Unai; Rass, Stefan; Pinzger, Martin; Maggi, Federico; Gil-Uriarte, Endika (Electronic Communications of the EASST, 2021)
As robots get damaged or security compromised, their components will increasingly require updates and replacements. Contrary to the expectations, most manufacturers employ planned obsolescence practices and discourage repairs to evade competition. We introduce and advocate for robot teardownas an approach to study robot hardware architectures and fuel security research. We show how our approach helps uncovering security vulnerabilities, and provide evidence of planned obsolescence practices